KONSEP KEPRIBADIAN GURU DALAM AL-QUR`AN - eulis habibah (Marifah: Jurnal Pendidikan dan Pemikiran Peradaban Islam, 2023)
The teacher is a obeyed and imitated figure, therefore a teacher should have a good personality. The Qur'an is a guide and a grip for Muslims. So it is fitting to know the concept of teacher personality in the Qur'an which will be discussed based on the letters of Ali Imran verses 104, 159, 186, asy-Syu'ara verses 214-217, and al-A'raf verse 29 Keywords: Teacher, Personality, and Al-Quran